PENERAPAN PRINSIP-PRINSIP EKONOMI SYARIAH DALAM PENGEMBANGAN USAHA KECIL DAN MENENGAH DI DESA KAYU LAUT MANDAILING NATAL - Jureid (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2024)
This study aims to examine the application of Islamic economic principles in the development of Small and Medium Enterprises (SMEs) in Kayu Laut Village, Mandailing Natal, with a focus on the local culinary sector. Despite facing challenges in terms of understanding and access to Sharia-based capital, SMEs in this village are beginning to integrate Sharia principles such as justice, transparency, and the prohibition of usury into their business practices. SME practitioners apply profit-sharing systems and maintain openness in transactions, contributing to the sustainability of the business and strengthening social relations with the surrounding community. This study found that the application of Islamic economic principles can enhance SME growth, create an ethical business environment, and improve social welfare. However, challenges such as limited knowledge and access to Sharia financial institutions remain obstacles that need to be addressed to maximize the potential for Sharia-based SME development in the region.